The effect of variable cutting depth and thickness on milling stability for orthogonal turn-milling. Issue 1 (January 2016) - Yan, Rong; Tang, Xiaowei; Peng, F.; Wang, Yong; Qiu, Feng
Abstract In orthogonal turn-milling processes, the workpiece and the tool rotate at the same time, which causes the cutting depth and thickness to change instantaneously, whereas the cutting depth is constant in conventional milling. Obviously, the stability model for conventional milling cannot be applied to orthogonal turn-milling. In this paper, a new two-dimensional stability model for orthogonal turn-milling is established in which both variable cutting depth and cross-coupling of the structural mode are considered. The stability lobe diagram is obtained using the full-discretization method. Based on abundant experimental data, we found that the variable cutting depth and cross-coupling of orthogonal turn-milling have an effect on the stability lobe diagram. A theoretical prediction that considers variable cutting depth and cross-coupling increases the stability boundary, and one such prediction is verified by the chatter experimental results.